Augmentation of endotoxin fever by recombinant human beta interferon in rabbits. - Kawasaki, H (1987)
Nonpyrogenic amounts of endotoxin (0.1 to 1 ng/kg), hardly detectable by conventional Limulus amoebocyte lysate tests, could produce a fever of around 1 degree C when injected with a nonpyrogenic dose (6 X 10(5) U/kg) of recombinant human beta interferon (IFN-beta) in rabbits. Release of endogenous IFN and tumor necrosis factor by endotoxin was also dramatically increased by recombinant human IFN-beta, and their levels in the blood were closely correlated with the increase of body temperature. These data suggest, if the synergism between IFN and endotoxin also operates in the homologous system (human IFN-human cells), that contaminating endotoxin in IFNs, even if not detectable by Limulus amoebocyte lysate test, can contribute to IFN fever to a considerable extent in humans.